Desarrollo de la ingeniería básica del proceso de producción del biodiesel a partir de la borra de café (2022)
In this research, whose purpose is to develop the basic engineering of the biodiesel production process from coffee grounds, an economic alternative to the biodiesel production currently carried out in the country is presented. This raw material, of which approximately 10,571,400 kg is found per year in Colombia, has the advantage (at least for the process) that it is almost entirely wasted and the advantage of not belonging to the food chain. In addition, it has been shown that the biodiesel obtained from the waste complies with the different standards, both national and international.